Предмет: Алгебра,
автор: adelina228337
Упростите выражение (обведённое ) пожалуйста!!!
Приложения:
parus77:
=(х+2)(9-х^2)+x^2(x+2)=(x+2)(9-x^2+x^2)=(x+2)*9=9x+18 (x^2 это х в квадрате)
Ответы
Автор ответа:
3
(х+2)(3-х)(3+х)+ х²(х+2) = (х+2)(9-х²)+ х²(х+2) = (х+2)(9-х²+ х²) = 9*(х+2) =9х+18
Похожие вопросы
Предмет: Биология,
автор: bakanbowena
Предмет: Українська мова,
автор: nc5csv29zs
Предмет: История,
автор: nnikich53
Предмет: История,
автор: Vika7088708
Предмет: Математика,
автор: animeshnik6